Mass spectrometric analysis of TRPM6 and TRPM7 from small intestine of omeprazole-induced hypomagnesemic rats - Kampuang, Nattida; Thongon, Narongrit (Frontiers in Oncology, 2022)
Disruption of small intestinal Mg2+ absorption has been reported as the underlying mechanism of proton pump inhibitor-induced hypomagnesemia (PPIH); hence, this study evaluated the expression, localization, phosphorylation, and oxidation of transient receptor potential melastatin 6 (TRPM6) and TRPM7 in the small intestine of rats subjected to PPIH. The expression and localization of cyclin M4 (CNNM4) was also analyzed. We show that, compared to control rats, membrane expression of the TRPM6/7 heterodimer and TRPM7 was markedly lower in the duodenum and the jejunum of PPIH rats; in contrast, expression of membrane TRPM6 and CNNM4 was higher in these organs. Mass spectrometric analysis of TRPM6 demonstrated hyper-phosphorylation, especially T1851, and hyper-oxidation at M1755, both of which can suppress its channel permeability. Further, hypo-phosphorylation of S141 and the dimerization motif domain of TRPM6 in PPIH rats might be involved in lower TRPM6/7 heterodimer expression. Hypo-phosphorylation, especially at S138 and S1360 in TRPM7 from PPIH rats disrupted stability of TRPM7 at the cell membrane; hyper-oxidation of TRPM7 was also observed. These results help explain the mechanism underlying the disruption of small intestinal Mg2+ absorption in PPIH.